Produção de ligno-hemi-celulases por fermentação em estado sólido e avaliação dos efeitos da aplicação das enzimas na composição química e estrutura do bagaço e da palha de cana - Moretti, Marcia Maria de Souza [UNESP] (2013)
This study investigated the effect of non expensive carbon and nitrogen sources on enzyme production by Myceliophthora thermophila M.7.7 in solid-state fermentation. Three kinds of lignocellulosic waste (corn straw, sugarcane bagasse and sugarcane straw) and six nitrogen sources (urea, calcium nitrate, analytical ammonium sulphate, yeast extract, agricultural fertilizer NPK 20-05-20 and fertilizing grade ammonium sulphate) were tested. Some physical-chemical parameters of the fermentation, such as temperature, initial pH and moisture content of the substrate on enzyme production were evaluated. Furthermore, the pre-treatment of bagasse and sugar cane straw with microwave radiation in presence of glycerol diluted in water, sulphuric acid and sodium hydroxide on the chemical composition, fiber structure and the efficiency of subsequent enzymatic hydrolysis was investigated. Bagasse and cane straw were subjected to 2 min of irradiation and the solid fractions resulting were used in the analysis of fibers, TGA, DTG, DSC, FTIR, X-ray and transmission electron microscopy and liquid fractions used to detemine sugar and phenol contents. Samples of bagasse, treated cane straw and untreated cane straw (control) were submitted to enzyme hydrolysis for 24 to 72 h at 55 °C with enzymatic solutions obtained by the cultivation of M. thermophila M.7.7. and Celluloclast 1.5L based on 60 U of endoglucanase activity per g of dry substrate or on the total amount of protein solutions (5 mg protein/g of dry substrate). The enzyme solution from M. thermophila M.7.7 was supplemented with a commercial β-glucosidase in order to achieve the same activity present in Celluclast. The maximum xylanase activity (446.9 U/ml), endoglucanase (94.7 U/ml) and β-glucosidase (2.8 U/mL) were obtained in the cultivation by SSF with 70% humidity, 40 °C using corn stover and wheat bran and nutrient solution composed of agricultural fertilizers, with pH adjusted to 5.0. ...